KONSEP TUJUAN PENDIDIKAN ISLAM DALAM ALQURAN SURAT AL-JUMU’AH AYAT 2 (Analisis Tafsir Al-Misbah Karya M. Quraish Shihab) - Nurul WD, Suci; Al Hamdani, M Djaswidi; Husni, H (Jurnal Penelitian Pendidikan Islam, 2015)
This research was conducted to analyze the concept of Islamic education objectives contained in the Qur'an in the verse al-Jumu'ah verse 2. The conclusions of the study are presented as follows: There are three objectives of Islamic Education, namely: first, individual goals, namely how each Muslim person changes in his attitude and actions in everyday life. Second, social goals through the stages in learning, namely the Prophet Muhammad. read the verses of Allah Almighty to his people, purify his people, and teach the Scriptures and al-Hikma and things that were not known beforehand. Third, the highest goal in Islamic education is in the form of devotion to God Almighty. manifested in individual goals and social goals in Islamic education.